The Politics of Chaos in the Middle East - Hunter, Shireen T. (A journal of church and state, 2009)
The Politics of Chaos in the Middle East is a slim volume by the well-known French expert on Islam and the Muslim World, especially South and Central Asia, Olivier Roy, translated from French. The book, which in reality is a long essay, deals with a wide array of subjects ranging from the nature of the American neo-conservatives' philosophy of interstate relations, their views on principles which should guide U.S. international behavior, to causes of the emergence of the Islamist movement in its various shades, and the reasons behind U.S. intervention in Iraq., Because of the book's shortness and the wide and varied range of issues it covers, inevitably the analysis of various subjects is insufficient and sometimes even simplistic.